Mass spectrometry based proteomics profiling of human monocytes. Issue 2 (22nd November 2016) - Zeng, Yong; Deng, Fei-Yan; Zhu, Wei; Zhang, Lan; He, Hao; Xu, Chao; Tian, Qing; Zhang, Ji-Gang; Zhang, Li-Shu; Hu, Hong-Gang; Deng, Hong-Wen
Abstract: Human monocyte is an important cell type which is involved in various complex human diseases. To better understand the biology of human monocytes and facilitate further studies, we developed the first comprehensive proteome knowledge base specifically for human monocytes by integrating both in vivo and in vitro datasets. The top 2000 expressed genes from in vitro datasets and 779 genes from in vivo experiments were integrated into this study. Altogether, a total of 2237 unique monocyte-expressed genes were cataloged. Biological functions of these monocyte-expressed genes were annotated and classified via Gene Ontology (GO) analysis. Furthermore, by extracting the overlapped genes from in vivo and in vitro datasets, a core gene list including 541 unique genes was generated. Based on the core gene list, further gene-disease associations, pathway and network analyses were performed. Data analyses based on multiple bioinformatics tools produced a large body of biologically meaningful information, and revealed a number of genes such as SAMHD1, G6PD, GPD2 and ENO1, which have been reported to be related to immune response, blood biology, bone remodeling, and cancer respectively. As a unique resource, this study can serve as a reference map for future in-depth research on monocytes biology and monocyte-involved human diseases.